1997
DOI: 10.1093/schbul/23.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and Psychophysiological Correlates of Psychosocial Functioning in Schizophrenia

Abstract: This study tested hypothesized relationships between neuropsychological and psychophysiological variables and concurrent levels of clinical and psychosocial functioning in schizophrenia. The sample consisted of 40 subjects diagnosed with a chronic schizophrenia spectrum disorder and living in community-based settings. The psychophysiological variables were tonic skin conductance (SC) level, SC reactivity to stressors, and SC response to orienting stimuli. The neuropsychological measures were the Stroop, the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(92 citation statements)
references
References 61 publications
(74 reference statements)
6
79
1
6
Order By: Relevance
“…The relationship between speed of processing and functioning found in the present study has also been described by other authors. Thus, speed of processing deficits have been associated with impairments in different domains of functional outcome such as global psychosocial functioning 60,67 , community functioning 68 , daily problem solving skills 69 , job tenure 70 , social skills 71 , or independent living skills 72 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between speed of processing and functioning found in the present study has also been described by other authors. Thus, speed of processing deficits have been associated with impairments in different domains of functional outcome such as global psychosocial functioning 60,67 , community functioning 68 , daily problem solving skills 69 , job tenure 70 , social skills 71 , or independent living skills 72 .…”
Section: Discussionmentioning
confidence: 99%
“…The association of cognitive function and subjective functioning has been repeatedly discussed and investigated. Contradictory hypotheses were favored in different publications [34] . First, that cognitive defi cits, especially attention and memory defi cits, are negatively associated with QOL and secondly, that patients with cognitive defi cits tend to report a better QOL, due to some insight defi cits.…”
Section: Discussionmentioning
confidence: 99%
“…Digit symbol coding also indexes the degree of functional disability that results from illness. Brekke et al 79 found coding task performance related to independent living. Stratta and colleagues 55 found the measure associated with scores on a scale measuring the level of performance in expected community roles.…”
Section: Commentmentioning
confidence: 99%